The management of hyperlipidemia - Ahmad H. Asdie, Ahmad H. Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
In terest in hyperlipidemia is related to its role in atherogenesis. The connection between bloodcholesterollevels and varibus manifestations of coronary heart disease has long been apparent.However, proof that this connecton is causal has been more elusive. For particular subpopulations it has been demonstrated that lowering elevated cholesterol levels can lead to fewer coronary heart disease events; this provides strong evidence of a causal relationship which can furthermore be favourably influenced.The significant lipid element contributing of plaque formation appears to be low density lipoprotein cholesterol, but its derivation in plaques in quite complicated. Low density lipoprotein and possibly intermediate density lipoprotein, with a somewhat lower cholesterol content, are known to enter sub-in finial spaces directly and they may do so in association whit cellular migration. Locally produced endothelial-derived relaxing factor.Despite the massive study on the subject of lipids, atherogenesis and its complications, much of our therapeutic endeavour still relates to hypothesis rather than established facts based on observations in humans. Key Words: hyperlipidemia - lipoproteins diet - physical exercise - antilipidemic drugs